STRATEGY ANALYSIS TO IMPROVE EMPLOYEE PERFORMANCE - Suprapto, Suprapto; Priyono, Priyono; Udjang, Raswan; Subarjo, Subarjo (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
Employees are a major asset in an organization that must be managed properly. The existence of human resource management is very important for organizations in managing, regulating, managing and using human resources so that they can function productively, effectively and efficiently to achieve the goals of the organization. The objectives of this research are (1) to examine and analyze the influence of work stress on employee performance, (2) to study and to analyze the influence of the work environment on employee performance, and (3) to study and analyze the influence of leadership style on employee performance. The number of samples used in the study were 122 respondents. The analytical tool used is the PASW (Predictive Analytics SoftWare), where the data processing uses the SPSS program. The results showed that work stress, work environment, and leadership style had a positive and significant effect on employee performance. Job stress has the greatest influence on employee performance, followed by work environment and leadership style. Work stress, work environment, and leadership style together have an effect of 82.3% on teacher performance, and the remaining 17.71% are influenced by other factors that are not explained in the study.